Fear of COVID‐19 Scale (FCV‐19S) across countries: Measurement invariance issues - Chung‐Ying Lin; Wen‐Li Hou; Mohammed A. Mamun; José Aparecido da Silva; Yunier Broche‐Pérez; Irfan Ullah; Akihiro Masuyama; Koubun Wakashima; Mélody Mailliez; Arnaud Carre; Yu‐Pin Chen; Kun‐Chia Chang; et al. (Wiley, 2021)
Abstract Aim The threats of novel coronavirus disease 2019 (COVID‐19) have caused fears worldwide. The Fear of COVID‐19 Scale (FCV‐19S) was recently developed to assess the fear of COVID‐19. Although many studies found that the FCV‐19S is psychometrically sound, it is unclear whether the FCV‐19S is invariant across countries. The present study aimed to examine the measurement invariance of the FCV‐19S across eleven countries. Design Cross‐sectional study. Methods Using data collected from prior research on Bangladesh (N = 8,550), United Kingdom (N = 344), Brazil (N = 1,843), Taiwan (N = 539), Italy (N = 249), New Zealand (N = 317), Iran (N = 717), Cuba (N = 772), Pakistan (N = 937), Japan (N = 1,079) and France (N = 316), comprising a total 15,663 participants, the present study used the multigroup confirmatory factor analysis (CFA) and Rasch differential item functioning (DIF) to examine the measurement invariance of the FCV‐19S across country, gender and age (children aged below 18 years, young to middle‐aged adults aged between 18 and 60 years, and older people aged above 60 years). Results The unidimensional structure of the FCV‐19S was confirmed. Multigroup CFA showed that FCV‐19S was partially invariant across country and fully invariant across gender and age. DIF findings were consistent with the findings from multigroup CFA. Many DIF items were displayed for country, few DIF items were displayed for age, and no DIF items were displayed for gender. Conclusion Based on the results of the present study, the FCV‐19S is a good psychometric instrument to assess fear of COVID‐19 during the pandemic period. Moreover, the use of FCV‐19S is supported in at least ten countries with satisfactory psychometric properties.